WEBINAR-BASED DENTAL HEALTH EDUCATION AT SD INSAN AMANAH - Diena Fuadiyah; Astika Swastirani; Fatima Fatima; Siti Halimah Laili Irwanti; Oswalda Rena Krismaningrat Laksono (Caring : Jurnal Pengabdian Masyarakat, 2023)
Background: In 2014-2018, the prevalence of dental caries occurrence in Indonesia was reportedly high. No less than 63% of Indonesian people, especially children, had suffered from the mouth and dental diseases; one of which was dental caries. Oral health is very important for the body, if oral hygiene is not maintained properly, it will cause various diseases in the oral cavity, such as periodontal disease and dental caries. Therefore, education is needed on dental health and mouth in order to avoid dental and mouth disease, especially during the Covid-19 pandemic. Promotive efforts can be done through daily oral health maintenance to support maximum health status during pandemic. One way to provide education is by using an online approach. The method of this study are providing education by webinar and assessing tests on dental and oral health knowledge in SD Insan Amanah Kota Malang. Aims: The purpose of this study was to see the effectiveness of online dental health education counseling on knowledge during the Covid-19 pandemic at elementary school. Methods: This research constitutes Quasy experimental. Samples were taken by purposive sampling, namely SD Insan Amanah class 3-6, with using the Wilcoxon test. Main Results: This study shows that dental health education counseling with a webinar method of effective knowledge with a sig p value of 0.056 (>0.05) which means there no change. There was not a statistical change, the data used a 95% confidence interval. Conclusion: The dental health education method for elementary school children with a webinar method isn’t significantly effective to improve knowledge about dental health.